Radio light curve of the galaxy possibly associated with FRB 150418 - Johnston, S.; Keane, E.; Bhandari, S.; Macquart, Jean-Pierre; Tingay, Steven; Barr, E.; Bassa, C.; Beswick, R.; Burgay, M.; Chandra, P.; Honma, M.; Kramer, M.; et al. (Oxford University Press, 2017)
We present observations made with the Australia Telescope Compact Array (ATCA), the Jansky Very Large Array (JVLA) and the Giant Metre-Wave Telescope of the radio source within the galaxy WISE~J071634.59-190039.2, claimed to be host of FRB~150418 by Keane et al. (2016). We have established a common flux density scale between the ATCA and JVLA observations, the main result of which is to increase the flux densities obtained by Keane et al. At a frequency of 5.5 GHz, the source has a mean flux density of 140uJy and is variable on short timescales with a modulation index of 0.36. Statistical analysis of the flux densities shows that the variations seen are consistent with refractive interstellar scintillation of the weak active galactic nucleus at the centre of the galaxy. It may therefore be the case that the FRB and the galaxy are not associated. However, taking into account the rarity of highly variable sources in the radio sky, and our lack of knowledge of the progenitors of FRBs as a class, the association between WISE~J071634.59-190039.2 and FRB~150418 remains a possibility.